2022
DOI: 10.1080/19490976.2022.2147055
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota composition as a candidate risk factor for dimethyl fumarate-induced lymphopenia in multiple sclerosis

Abstract: Mounting evidence points towards a pivotal role of gut microbiota in multiple sclerosis (MS) pathophysiology. Yet, whether disease-modifying treatments alter microbiota composition and whether microbiota shape treatment response and side-effects remain unclear. In this prospective observational pilot study, we assessed the effect of dimethyl fumarate (DMF) on gut microbiota and on host/microbial metabolomics in a cohort of 20 MS patients. Combining state-of-the-art microbial sequencing, metabolome mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…With regard to DMF, one of the pilot studies 27 failed to link microbial composition with gastrointestinal complaints, common in the early phase of treatment. Interestingly, in another study, 130 it was found that a particular baseline microbiome signature (presence of A. muciniphila and absence of P. copri ) could predict occurrence of lymphopenia, a relevant side effect of DMF.…”
Section: Impact Of Disease-modifying Treatment On the Gut Microbiome ...mentioning
confidence: 97%
See 1 more Smart Citation
“…With regard to DMF, one of the pilot studies 27 failed to link microbial composition with gastrointestinal complaints, common in the early phase of treatment. Interestingly, in another study, 130 it was found that a particular baseline microbiome signature (presence of A. muciniphila and absence of P. copri ) could predict occurrence of lymphopenia, a relevant side effect of DMF.…”
Section: Impact Of Disease-modifying Treatment On the Gut Microbiome ...mentioning
confidence: 97%
“…Pathways of bacterial metabolism of retinol and methane were identified as targets of DMF and GA. 123 As fumarates are degraded in the citrate cycle, an increase in late citrate cycle intermediates was observed during treatment with DMF, both in the patients’ serum and in the gut microbes’ metabolism. 130 The inhibitory effect of DMF on Clostridium perfringens growth was neutralized by glutathione (having anti-oxidative properties), which suggests modulation of oxidative stress as another potential link between DMT and bacteria. 128 Findings from a large panel of metabolomic analysis in serum and stools of MS patients 41 demonstrated that pathways related to synthesis of lysine, L-ornithine, sugar nucleotides and unsaturated fatty acids were specifically modulated by particular DMTs.…”
Section: Impact Of Disease-modifying Treatment On the Gut Microbiome ...mentioning
confidence: 99%
“…Recent evidence suggests a potential connection between the adverse effects of DMF treatment and its effects on gut microbiota. Changes in the composition of gut microbiota under DMF treatment have been indeed proposed as potential risk factors for lymphopenia ( Diebold et al, 2022 ) and GI tract symptoms ( Storm-Larsen et al, 2019 ). On the other hand, both preclinical studies on in vivo models and clinical studies on psoriasis patients have demonstrated some benefic properties exerted by DMF on the composition of the microbiota ( Eppinga et al, 2017 ; Ma et al, 2017 ), suggesting a more complex interaction between the two.…”
Section: Novel Potential Pharmacological Applicationsmentioning
confidence: 99%
“…On MS patients, several clinical studies on subjects undergoing DMF treatment analysed the composition of the gut microbiome ( Katz Sand et al, 2019 ; Storm-Larsen et al, 2019 ; Diebold et al, 2022 ; Ferri et al, 2023 ), observing changes in the relative abundance of different subpopulations. Some of the detected DMF-induced alterations, e.g., decreases in Clostridium ( Ferri et al, 2023 ) and proinflammatory taxa like A. muciniphilia and C. eutactus levels and increases in anti-inflammatory species like L. pentosus ( Diebold et al, 2022 ), potentially suggest that a positive modulation of the gut microbiome could represent an additional therapeutic mechanism of DMF.…”
Section: Novel Potential Pharmacological Applicationsmentioning
confidence: 99%
“…Several studies have suggested that alterations in the composition of the gut microbiota [114]-the intersection between the host and the environment-is one major trigger of MS and a significant contributor to disease progression in MS patients [17,[115][116][117][118][119][120].…”
Section: The Microbiome and Regulatory Gut-mucosal Iga + B Cells In N...mentioning
confidence: 99%